Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I've been trying to simplify this equation:

Y = (¬AB + ¬C)(¬A + ¬D)

.. into this equation.

Y  = ¬A¬C + ¬C¬D + ¬AB

Unfortunately I keep going in circles with expanding and minimizing the booleans. Any tips or advice? Thanks.

share|cite|improve this question… won't show you the steps it took to get all its answers, but may come in handy at some point... – MatrixFrog Oct 14 '10 at 9:54
up vote 1 down vote accepted

Use the following simplification:

$\neg AB(\neg A + \neg D) = \neg AB\neg A + \neg AB\neg D = \neg AB + \neg AB\neg D = \neg AB$.

share|cite|improve this answer
Wow I realize I made a terrible mistake. I was cancelling ¬A¬AB because for some reason I thought ¬A¬A = 0 when in fact ¬A¬A = ¬A. Ugh.... thanks for the help! – Sam Oct 14 '10 at 3:42

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.